Leadership and the implementation of strategic plans - Masufi, Dilahloane Monica; MASUFI, DILAHLOANE MONICCA (My University, 2012)
People around the world have basic needs that have to be met; one of those needs is the need for protection. People need to feel safe and secure in their environments and in their homes. In South Africa the South African Police Service is tasked with the responsibility to ensure that people are, and feel, safe. To realize this need of protecting the people, a strategy that will detail how the citizens will be protected is necessary. To implement the strategy, capable leadership is necessary to ensure that the strategic plan is successfully implemented. Leadership style and personal relationships play a vital role in implementing the strategy. The type of leadership at each station will determine whether the station succeeds or fails in operationalizing the strategy, hence a distinction in the province between the poor performing stations and the best performing stations. There are also leadership strategies for consideration in the implementation of strategic plans in SAPS. For example, the leadership has to give serious consideration to the issues of the structure, police culture, resources, to ensure that there is proper alignment between the resources and the structure, over and above the leadership style and type. This study investigates the leadership style at the Rabie Ridge Police Station and how their leadership style impacts on the implementation of the strategic plans as well as challenges encountered when implementing the strategic plans, to ensure that the citizens are, and feel, safe. This was explored from the transfomational Leadership theory perspective. The study employed a qualitative approach and designed a semistructured questionnaire for in-depth interviews with the intention to solicit responses. The research demonstrated that there is team work and commitment by the members at the station in implementing their strategic plans, hence their good performance as demonstrated by the SAPS performance chart. The study also showed that there is a challenge incommunication as most respondents seldom meet with their leadership. It is therefore recommended that there be enhancement of communication skills to ensure proper communication as well as the encouragement of open door policy for members to share any dissatisfaction with their leadership
MM thesis - P&DM
Keywords: Leadership; South African Police Service; Strategy